2021
DOI: 10.1080/00365513.2021.1941235
|View full text |Cite
|
Sign up to set email alerts
|

Mild impairment of renal function (shrunken pore syndrome) is associated with increased risk of a future first-ever myocardial infarction in women

Abstract: Hultdin (2021): Mild impairment of renal function (shrunken pore syndrome) is associated with increased risk of a future first-ever myocardial infarction in women,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The selectively accumulated proteins consist of cytokines, hormones, growth factors, and signaling peptides, many of which have proatherosclerotic effects as corroborated by proteomic studies [ 33 , 34 ]. Accordingly, most studies concerning SPS demonstrated adverse cardiovascular endpoints [ 19 , 20 , 35 ]. However, few studies conducted so far related SPS to renal outcomes, and our study was the first one to our knowledge that assess the relationship between SPS and ESRD or eGFR decline in patients suffering kidney diseases of known pathological diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The selectively accumulated proteins consist of cytokines, hormones, growth factors, and signaling peptides, many of which have proatherosclerotic effects as corroborated by proteomic studies [ 33 , 34 ]. Accordingly, most studies concerning SPS demonstrated adverse cardiovascular endpoints [ 19 , 20 , 35 ]. However, few studies conducted so far related SPS to renal outcomes, and our study was the first one to our knowledge that assess the relationship between SPS and ESRD or eGFR decline in patients suffering kidney diseases of known pathological diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Both 60% and 70% eGFRcys/eGFRcr ratio have been used in previous studies [ 14 , 15 , 17 ]. Continuous ratio has also been explored in some researches where the above cut-off values identified few patients [ 19 , 20 , 36 ]. We chose the cut-off value of 70% as previous studies have shown that adverse effects already come into play in early stage when eGFRcys/eGFRcr ratio falls to 85% or 90% [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the pore model for glomerular filtration [72,73], these observations could be explained by a shrinking (or elongation) of the pores [71]. Almost immediately after this observation, the presence of shrunken pore syndrome and/or an eGFR cystatin C /eGFR creatinine -ratio significantly below 1 was found to be strongly correlated to mortality, morbidity, heart failure and end-stage renal disease [63,[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]. Similar observations between an abnormally low eGFR cystatin C /eGFR creatinine -ratio and morbidity have recently been described in an American study, although it used the difference between eGFR cystatin C and eGFR creatinine to identify a specific reduction in the excretion of 5-30 kDa molecules [89,90].…”
Section: The Missing Piece Of the Puzzle -Shrunken Or Elongated Pore ...mentioning
confidence: 99%